On the origin of computational model sensitivity, error, and uncertainty in threaded fasteners. (1st July 2017) - Castelluccio, G.M.; Brake, M.R.W.
Highlights: We compare 1D, 2.5D and 3D finite element models of threaded fasteners. Major limitations appear for reproducing realistic responses in 2.5D models. Elasto-plastic properties dominate the mechanical response nonlinearity. A regularized resisting length controls the elastic displacement. Abstract: Predicting the mechanical response of components requires simplifications and idealizations that affect the fidelity of the results and introduce errors. Some errors correspond to the limited knowledge of intrinsic physical attributes while others are introduced by the modeling framework and mathematical approximations. This paper studies the dependence of the force-displacement response of threaded fasteners on modeling attributes such as geometry, material, and friction resistance using finite element simulations. A systematic comparison of 1 D, 2.5 D or 3 D computational models demonstrates the influence of model properties and the limitations of the methodologies. Finally, the paper discusses the sources of model inputs and model form errors for threaded fasteners.